Touch interaction based on 3D air traffic visualization system - Zhong, Xin (2017)
With the number of people travelled by plane increase rapidly these decades, the working load of the air traffic controllers (ATCOs) becomes heavier, and it is highly expected that the ATCOs have been familiar with the current Air Traffic Control System(ATCS) and deal with different kinds of control issues efficiently. The radar display widely used now is the 2-Dimensional (2D) planar display, which is stable but there still exists vision restriction. Therefore, the 3-Dimensional(3D) visualization is suggested to be applied in the ATCS. Since the 3D control system has not been developed maturely, the objective of this project is to research and prototype a possible model of touch interaction based 3D control system. This control system is written in web based programming languages like HTML, CSS, and JavaScript. A touchscreen is used for the interaction testing. Extensive literature reviews have been conducted to understand the real working system of ATCOs, 2D & 3D air traffic visualization and flight strip information. A touch interaction based 3D control system prototype was assembled. Future research areas and improvements have been suggested at the end of this project.